Reversible sorption of carbon dioxide in Ca-Mg-Fe systems for thermochemical energy storage applications - Desage, Lucie; Humphries, Terry; Paskevicius, Mark; Buckley, Craig (2024)
Alternatives to fossil fuels are necessary to reduce greenhouse gas emissions, and energy storage is crucial to transition to renewable energy. Thermochemical energy storage is one option to store energy for 24/7 utilisation, and as such, the reversible carbonation of the Ca : Mg : Fe oxide system was investigated to determine its feasibility as a thermochemical energy storage material. The Ca : Mg : Fe (1 : 1 : 1) sample synthesised from co-crystallisation of metal acetates retained reversible CO2 sorption at 90% over 100 cycles, thus the associated physical properties were thoroughly investigated. Powder X-ray diffraction analyses indicated the formation of dicalcium ferrite and magnesioferrite, respectively in the decarbonated and carbonated states, which suggested a synergistic effect enhancing the reversible sorption of CO2 in the 2CaO·Fe2O3·MgO intermediate system involved in the reaction mechanism. The thermodynamics of the reactions were determined using pressure-composition-isotherm measurements, resulting in calculated enthalpies and entropies of ΔHabs = −146 ± 5 kJ mol−1 and ΔSabs = −141 ± 5 J mol−1 K−1, and ΔHdes = 178 ± 4 kJ mol−1 and ΔSdes = 167 ± 4 J mol−1 K−1 for CO2 absorption and desorption, respectively. The application of the Kissinger method determined an activation energy of 203 ± 14 kJ mol−1 for the decarbonation reaction. The maximum energy storage density of the system was evaluated to be 468 kJ kg−1 with an operating temperature of ≈750 °C. Overall, the Ca-Mg-Fe system can integrate thermochemical batteries and is promising to promote thermochemical energy storage for backing up power production using renewables.